Water-retention slow-release fertilizer granules for promoting growth of plant lines and preparation method of water-retention slow-release fertilizer granules
By using materials such as CMC, NaAlg and UF to construct a physical/chemical dual crosslinking network structure, water-retaining and slow-release fertilizer particles that promote plant growth were prepared, which solved the problem of unpredictable and high cost of existing slow-release fertilizers, and achieved good sustained-release effect and biodegradability.
Patent Information
- Application Number
- CN202411962858.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
AI Technical Summary
The existing sustained-release fertilizers have problems with unpredictable release rates and high cost. Traditional highly absorbed polymers have poor salt tolerance and high cost, making it difficult to develop new environmentally friendly, degradable, and low-cost water-retaining and sustained-release fertilizers.
Carboxymethylcellulose (CMC) and sodium alginate (NaAlg) were used as the backbone material, combined with urea-formaldehyde resin (UF) as the sustained-release nitrogen source, and citric acid as the crosslinking agent to construct a physical/chemical dual crosslinking network structure to prepare water-retaining and sustained-release fertilizer particles that promote plant growth.
It achieves good mechanical strength and sustained release effect, and has good biodegradability, is environmentally friendly and reduces production costs.
Smart Images

Figure CN119638516A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of slow-release fertilizers, and more specifically, to a water-retaining slow-release fertilizer particle for promoting plant growth and a preparation method thereof. Background Art
[0002] With the increase in population and environmental pollution, improving agricultural productivity to meet food demand has become an urgent task; fertilization is an important measure to increase crop yields, but excessive fertilization and low fertilizer utilization rate lead to resource waste and environmental problems; slow-release fertilizers improve fertilizer utilization rate by controlling the nutrient release rate; but traditional slow-release fertilizers have problems such as unpredictable release rate and high cost; super absorbent polymers (SAP) can improve water resource utilization, but have poor salt tolerance and high cost; therefore, it is of great significance to develop new water-retaining slow-release fertilizers that are environmentally friendly, degradable and low-cost.
[0003] In view of this, we propose a water-retaining slow-release fertilizer granule for promoting plant growth and a preparation method thereof. Summary of the invention
[0004] The purpose of the present application is to provide a water-retaining slow-release fertilizer granule for promoting plant growth and a preparation method thereof, which solves the technical problems existing in the above-mentioned prior art.
[0005] The present application provides a water-retaining slow-release fertilizer granule for promoting plant growth, which is composed of the following components:
[0006] Carboxymethyl cellulose (denoted as: CMC);
[0007] Sodium alginate (denoted as: NaAlg);
[0008] Urea-formaldehyde resin (denoted as: UF);
[0009] Citric acid (denoted as: CA);
[0010] The amount of CMC accounts for 2-7.5wt.% of the mass of the aqueous solution, the amount of NaAlg accounts for 0.5-7.5wt.% of the mass of the aqueous solution, the amount of UF accounts for 0.5-4wt.% of the mass of the aqueous solution, and the amount of CA accounts for 0.2-2.5wt.% of the total mass of CMC, NaAlg and UF.
[0011] The present application also provides a method for preparing the above-mentioned water-retaining slow-release fertilizer particles for promoting plant growth, comprising the following steps:
[0012] S1, preparing urea-formaldehyde resin (UF);
[0013] S2, preparing CMC, NaAlg, UF and sodium dodecyl sulfate (SDS) into an aqueous solution and performing a gelatinization reaction;
[0014] S3, adding citric acid (CA) to carry out polycondensation cross-linking reaction;
[0015] S4, pouring the solution into a mold, letting it stand and washing it, and finally freeze-drying it to obtain water-retaining slow-release fertilizer granules.
[0016] As an optional solution of the technical solution of this application document, S1 includes the following steps:
[0017] S1.1: preparing an aqueous solution of urea and formaldehyde (FA), adding sodium hydroxide to adjust the pH value, and performing an addition reaction to generate hydroxymethyl urea;
[0018] S1.2: adding phosphoric acid to adjust the pH value and performing polycondensation reaction to generate UF resin;
[0019] S1.3: Wash the UF resin with anhydrous ethanol and freeze-dry it.
[0020] As an optional solution of the technical solution of the present application document, the S1.1 comprises: preparing urea and FA into an aqueous solution of 18-20wt.% (the molar ratio of urea to formaldehyde is U:F=1:2);
[0021] Among them, urea accounts for 8-10wt.% of the aqueous solution, FA accounts for 8-10wt.% of the aqueous solution, NaOH (0.001mol / L) is added dropwise to adjust the pH of the reaction system to 8-10, and the addition reaction is carried out at a temperature of 50°C for 2h to generate hydroxymethyl urea.
[0022] As an optional solution of the technical solution of the present application document, the concentrations of the urea (urea) and the formaldehyde aqueous solution (FA) are both 9-9.5wt.%.
[0023] As an optional solution of the technical solution of the present application document, the S1.2 comprises: adding phosphoric acid (0.001 mol / L) to adjust the pH of the reaction system to 4-6, and performing polycondensation reaction at a temperature of 90° C. for 2 hours;
[0024] During the polycondensation reaction, a white granular precipitate is generated.
[0025] As an optional solution of the technical solution of this application document, S2 includes:
[0026] S2.1: CMC, NaAlg and UF are prepared into a 3.5-25wt.% aqueous solution, wherein CMC accounts for 2-7.5wt.% of the mass of the aqueous solution, NaAlg accounts for 0.5-7.5wt.% of the mass of the aqueous solution, and UF accounts for 0.5-2.5wt.% of the mass of the aqueous solution;
[0027] S2.2: Add 0.5-1.5wt.% of SDS to the aqueous solution and gelatinize in a 60℃ water bath for 3h.
[0028] As an optional solution of the technical solution of this application document, the concentration of the CMC aqueous solution is 5-7.5wt.%, the concentration of the NaAlg aqueous solution is 0.5-1.5wt.%, the concentration of the UF aqueous solution is 0.5-1.5wt.%, and the concentration of the SDS aqueous solution is 1-1.5wt.%;
[0029] During the reaction, fine white foam appeared in the system.
[0030] As an optional solution of the technical solution of this application document, S3 includes:
[0031] S3.1: Take CA and put it into a beaker and add 10 ml of distilled water to dissolve it and add it into the system; wherein the amount of CA is 0.2-2.5wt.% of the total mass of CMC, NaAlg and UF;
[0032] S3.2: After heating to 80°C, polycondensation and crosslinking reaction were carried out for 3 hours; during the reaction, the white foam in the system decreased.
[0033] As an optional solution of the technical solution of this application document, S4 includes:
[0034] S4.1. After the reaction is completed, pour the solution into a mold and let it stand at room temperature for 1 hour;
[0035] S4.2, washing and separation with excess anhydrous ethanol;
[0036] S4.3. Place in freeze dryer and dry for 48 hours. The obtained product material is named CMC-NaAlg / UF.
[0037] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0038] The present application adopts carboxymethyl cellulose (CMC) and sodium alginate (NaAlg) as skeleton materials. These two materials are widely available, inexpensive, and easily degraded, and will not cause secondary pollution to the soil. Urea-formaldehyde resin (UF) is introduced as a slow-release nitrogen source, and citric acid is used as a cross-linking agent to construct a physical / chemical double cross-linked network structure to improve mechanical strength and slow-release effect. At the same time, it has good biodegradability and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a flow chart of the preparation process of CMC-NaAlg / UF water-retaining and slow-release fertilizer particles disclosed in a preferred embodiment of the present application;
[0040] Figure 2 A diagram of the synthesis mechanism of a UF reaction disclosed in a preferred embodiment of the present application;
[0041] Figure 3 This is a CMC-NaAlg / UF reaction mechanism diagram disclosed in a preferred embodiment of the present application;
[0042] Figure 4 The FT-IR spectrum disclosed in a preferred embodiment of the present application;
[0043] Figure 5 The XRD pattern disclosed in a preferred embodiment of the present application;
[0044] Figure 6 This is the XPS total spectrum disclosed in a preferred embodiment of the present application;
[0045] Figure 7 A C1s fine spectrum disclosed in a preferred embodiment of the present application;
[0046] Figure 8 The XPS total spectrum element content disclosed in a preferred embodiment of the present application;
[0047] Fig. 9 The UF single factor experimental results disclosed in a preferred embodiment of the present application;
[0048] Fig.10 The element content of CMC-NaAlg / UF disclosed in a preferred embodiment of the present application;
[0049] Fig.11 This is the sustained release curve of CMC-NaAlg / UF in still water disclosed in a preferred embodiment of the present application;
[0050] Fig.12 This is the degradation curve of CMC-NaAlg / UF in sandy soil disclosed in a preferred embodiment of the present application; DETAILED DESCRIPTION
[0051] The present application is further described in detail below in conjunction with the accompanying drawings.
[0052] Embodiment 1
[0053] Reference Figure 1-Figure 12 The present application discloses a water-retaining slow-release fertilizer granule for promoting plant growth, which is composed of the following components:
[0054] Carboxymethyl cellulose (denoted as: CMC);
[0055] Sodium alginate (denoted as: NaAlg);
[0056] Urea-formaldehyde resin (denoted as: UF);
[0057] Citric acid (denoted as: CA);
[0058] The amount of CMC accounts for 2-7.5wt.% of the mass of the aqueous solution, the amount of NaAlg accounts for 0.5-7.5wt.% of the mass of the aqueous solution, the amount of UF accounts for 0.5-4wt.% of the mass of the aqueous solution, and the amount of CA accounts for 0.2-2.5wt.% of the total mass of CMC, NaAlg and UF.
[0059] The present application also discloses a method for preparing the above-mentioned water-retaining slow-release fertilizer particles for promoting plant growth, comprising the following steps:
[0060] S1, preparing urea-formaldehyde resin (UF);
[0061] S2, preparing CMC, NaAlg, UF and sodium dodecyl sulfate (SDS) into an aqueous solution and performing a gelatinization reaction;
[0062] S3, adding citric acid (CA) to carry out polycondensation cross-linking reaction;
[0063] S4, pouring the solution into a mold, letting it stand and washing it, and finally freeze-drying it to obtain water-retaining slow-release fertilizer granules.
[0064] The S1 comprises the following steps:
[0065] S1.1: preparing an aqueous solution of urea and formaldehyde (FA), adding sodium hydroxide to adjust the pH value, and performing an addition reaction to generate hydroxymethyl urea;
[0066] S1.2: adding phosphoric acid to adjust the pH value and performing polycondensation reaction to generate UF resin;
[0067] S1.3: Wash the UF resin with anhydrous ethanol and freeze-dry it.
[0068] The step S1.1 comprises: preparing urea and FA into an aqueous solution of 18-20wt.% (the molar ratio of urea to formaldehyde is U:F=1:2); wherein urea accounts for 8-10wt.% of the aqueous solution, and FA accounts for 8-10wt.% of the aqueous solution; dropping NaOH (0.001mol / L) to adjust the pH of the reaction system to 8-10, and performing an addition reaction at a temperature of 50°C for 2h to generate hydroxymethyl urea. The concentrations of the urea (urea) and formaldehyde aqueous solution (FA) are both 9-9.5wt.%.
[0069] The S1.2 comprises: adding phosphoric acid (0.001 mol / L) to adjust the pH of the reaction system to 4-6, and carrying out a polycondensation reaction at a temperature of 90° C. for 2 hours; wherein, during the polycondensation reaction, a white granular precipitate is generated.
[0070] The S2 includes:
[0071] S2.1: CMC, NaAlg and UF are prepared into a 3.5-25wt.% aqueous solution, wherein CMC accounts for 2-7.5wt.% of the mass of the aqueous solution, NaAlg accounts for 0.5-7.5wt.% of the mass of the aqueous solution, and UF accounts for 0.5-2.5wt.% of the mass of the aqueous solution;
[0072] S2.2: Add 0.5-1.5wt.% of SDS to the aqueous solution and gelatinize in a 60℃ water bath for 3h.
[0073] As an optional solution of the technical solution of this application document, the concentration of the CMC aqueous solution is 5-7.5wt.%, the concentration of the NaAlg aqueous solution is 0.5-1.5wt.%, the concentration of the UF aqueous solution is 0.5-1.5wt.%, and the concentration of the SDS aqueous solution is 1-1.5wt.%; wherein, fine white foam appears in the system during the reaction process.
[0074] The S3 includes:
[0075] S3.1: Take CA and put it into a beaker and add 10 ml of distilled water to dissolve it and add it into the system; wherein the amount of CA is 0.2-2.5wt.% of the total mass of CMC, NaAlg and UF;
[0076] S3.2: After heating to 80°C, polycondensation and crosslinking reaction were carried out for 3 hours; during the reaction, the white foam in the system decreased.
[0077] The S4 includes:
[0078] S4.1. After the reaction is completed, pour the solution into a mold and let it stand at room temperature for 1 hour;
[0079] S4.2, washing and separation with excess anhydrous ethanol;
[0080] S4.3. Place in freeze dryer and dry for 48 hours. The obtained product material is named CMC-NaAlg / UF.
[0081] The preparation method of the above-mentioned water-retaining slow-release fertilizer granules for promoting plant growth is as follows:
[0082] Materials Needed:
[0083] Carboxymethyl cellulose (CMC): purity ≥98%
[0084] Sodium alginate (NaAlg): purity ≥98%
[0085] Urea
[0086] Formaldehyde aqueous solution (FA): 37% aqueous solution
[0087] Citric acid (CA)
[0088] Sodium dodecyl sulfate (SDS): analytical grade
[0089] Anhydrous ethanol
[0090] Deionized water
[0091] Equipment needed:
[0092] Constant temperature water bath
[0093] Vacuum freeze dryer
[0094] Electronic balance
[0095] Mortar
[0096] Beaker
[0097] Mould
[0098] Preparation steps:
[0099] Preparation of urea-formaldehyde resin (UF):
[0100] Add 100 g of urea and 100 g of formaldehyde aqueous solution into a beaker, and add deionized water to a total volume of 500 mL.
[0101] Add 0.5 mL of 0.001 mol / L sodium hydroxide solution and adjust the pH value to 8-10.
[0102] The beaker was placed in a constant temperature water bath at 50°C, stirred at a speed of 300 r / min, and reacted for 2 hours.
[0103] Add 0.5 mL of 0.001 mol / L phosphoric acid solution and adjust the pH value to 4-6.
[0104] The beaker was placed in a constant temperature water bath at 90°C, stirred at a speed of 300 r / min, and reacted for 2 hours.
[0105] After the reaction, the white precipitate was repeatedly washed with anhydrous ethanol to remove residual water and unreacted substances.
[0106] The washed white particles were freeze-dried in vacuum for 24 hours to obtain UF resin.
[0107] Preparation of CMC-NaAlg / UF water-retaining slow-release fertilizer granules:
[0108] 50 g CMC, 10 g NaAlg, 10 g UF and 2 g SDS were added into a beaker and deionized water was added to make the total volume 200 mL.
[0109] The beaker was placed in a constant temperature water bath at 60°C, stirred at a speed of 300 r / min, and reacted for 3 hours.
[0110] Add 2 g of citric acid into a beaker, add 10 mL of deionized water to dissolve, and add the solution into the system.
[0111] The beaker was placed in a constant temperature water bath at 80°C, stirred at a speed of 300 r / min, and reacted for 3 hours.
[0112] After the reaction is completed, the solution is poured into a mold and allowed to stand at room temperature for 1 hour.
[0113] The particles were washed and separated with excess anhydrous ethanol and dried in a freeze dryer for 48 hours to obtain CMC-NaAlg / UF water-retaining and slow-release fertilizer particles.
[0114] Performance Test:
[0115] Water absorption performance test: The water absorption rate of the water-retaining slow-release fertilizer granules was measured by the tea bag method, and the result was 185.9, as follows:
[0116] Place 1g of super absorbent polymer powder in a tea bag and immerse it completely in distilled water. Substitute the values into (1) at regular intervals to measure its free absorption capacity until equilibrium is reached (24h). Calculate the water absorption rate according to the following formula: ; Wherein, W is the water absorption ratio; m0 is the mass of the sample when dried; and m is the mass of the gel when the swelling equilibrium is reached. Due to the low strength of CMC-SA gel, it is unstable and fragile in aqueous solution; and UF resin contains a large number of -NH- groups, which adsorb to the surface of the adherend through intermolecular forces (such as van der Waals forces, hydrogen bonds, etc.), produce bonding, and are easily physically entangled with the material. Through the IPN technology, the UF molecular chain is entangled with CMC-SA to form physical crosslinks, so that the CMC-SA / UF gel has better mechanical strength and nutrient sustained release function. As shown in the attached Fig. 9 As shown in the figure, the water absorption rate increases first and then decreases with the increase of UF concentration. And when the concentration exceeds 15wt.%, the water absorption rate drops rapidly. When the UF concentration is 15wt.%, the maximum water absorption rate is 185.9; when the UF concentration is low, the introduction of UF resin increases the crosslinking degree of CMC-SA / UF, which increases the gel strength; when CMC-SA / UF absorbs water, the crosslinking network is not destroyed and the network is stretched. As the UF concentration increases, the excess UF resin causes excessive crosslinking, the gel network is insufficient to stretch, and the pores are blocked.
[0119] Slow-release performance test: The Kjeldahl nitrogen method was used to determine the nitrogen content of the water-retaining slow-release fertilizer granules, and the cumulative slow-release rate was calculated. The results showed that the granules had a good slow-release effect. The details are as follows:
[0120] 1.0 g of dried CMC-NaAlg / UF and 10 mL of deionized water were added to a 100 mL beaker. 1 ml of the leachate was extracted at predetermined time intervals. To keep the volume constant, 1 ml of fresh deionized water was added to the above system and then briefly homogenized again. Subsequently, the nitrogen content was measured by titration using the Kjeldahl method. Fig.10 The nitrogen content of the material obtained by the element analyzer can be used to infer the overall nitrogen content and to determine the sustained release rate. Fig.11 is the cumulative sustained release rate of CMC-NaAlg / UF in static water. Since UF is a polymer, the sustained release of nitrogen is delayed. In addition, polymerization plays a key role in this process because the release time and the equilibrium value of more than 100h directly depend on the content of the polymer. And the release rate of CMC-NaAlg / UF material is greater than 100h, which has a good sustained release effect.
[0121] Degradability test: The water-retaining slow-release fertilizer particles were buried in the soil, taken out and weighed regularly, and the degradation rate was calculated. The results showed that the particles had good biodegradability. The details are as follows:
[0122] 2g of composite material was placed in a nylon tea bag and buried in soil (taken from typical sandy soil in Yulin area) at a depth of 5cm for biodegradation experiment. 500g of tap water was used to irrigate the soil regularly every 3 days. Samples were taken out every 7 days, washed with distilled water, dried at 60℃ until the mass did not change, and weighed. The biodegradation rate of the coating material was calculated as follows: Where Wt is the net weight of the composite material, W0 and Wt0 are the weights before and after the membrane is buried in the soil, respectively. Fig.12 CMC-NaAlg / UF water-retaining slow-release fertilizer has a good degradation effect in sandy soil, and the degradation rate in 42 days can reach 30%. It is friendly to the biological environment and will not cause secondary damage to the soil.
[0123] Embodiment 2
[0124] Materials Needed:
[0125] Same as the first embodiment.
[0126] Preparation steps:
[0127] The amounts of CMC, NaAlg, UF and SDS were adjusted to 5 g, 1 g, 1 g and 1 g, respectively, and the other steps were the same as those in Example 1.
[0128] Performance Test:
[0129] The water absorption ratio is 183.5, and the sustained-release performance and degradation performance are similar to those in Example 1.
[0130] Embodiment 3
[0131] Materials Needed:
[0132] Same as the first embodiment.
[0133] Preparation steps:
[0134] The dosage of citric acid was adjusted to 1 g, and the other steps were the same as those in Example 1.
[0135] Performance Test:
[0136] The water absorption ratio is 180.2, and the sustained-release performance and degradation performance are similar to those in Example 1.
[0137] Embodiment 4
[0138] Materials Needed:
[0139] Same as the first embodiment.
[0140] Preparation steps:
[0141] The amount of UF was adjusted to 15 g, and the other steps were the same as those in Example 1.
[0142] Performance Test:
[0143] The water absorption ratio is 185.9, and the sustained-release performance and degradation performance are similar to those in Example 1.
[0144] Embodiment 5
[0145] Materials Needed:
[0146] Same as the first embodiment.
[0147] Preparation steps:
[0148] The amount of SDS was adjusted to 1.5 g, and the other steps were the same as in Example 1.
[0149] Performance Test:
[0150] The water absorption ratio is 184.5, and the sustained-release performance and degradation performance are similar to those in Example 1.
[0151] In summary, the water-retaining slow-release fertilizer particles for promoting plant growth disclosed in the embodiments of the present application use ternary weak acid citric acid as a chemical crosslinking agent, UF resin to achieve physical crosslinking, physical / chemical double crosslinking mode, and construct a semi-interpenetrating network structure to achieve slow release of nutrients. Hydrogel as a fertilizer carrier can enable CMC-NaAlg / UF water-retaining slow-release fertilizer to retain moisture when applied to the soil, highlighting the water-fertilizer coupling effect, which is beneficial to crop growth;
[0152] And it has good economic benefits. It is estimated that the material cost of 1 ton of carboxymethyl cellulose in the market is about RMB 6,000; the material cost of 1 ton of sodium alginate is about RMB 4,020. The material cost of 1 ton of acrylic acid, the main material of traditional commercial water-retaining agent, is about RMB 8,200. The present invention has the advantages of low chromium price and renewable and easy-to-prepare raw materials. Compared with acrylic acid, the materials used in the present invention are easier to degrade and will not cause secondary pollution to the soil. And with abundant resources, wide sources and low prices of carboxymethyl cellulose and soluble starch as the main raw materials, it provides a new way for the high added value utilization of carboxymethyl cellulose and sodium alginate.
Claims
1. A water-retaining slow-release fertilizer granule for promoting plant growth, characterized in that: It is composed of the following components: Carboxymethyl cellulose (denoted as: CMC); Sodium alginate (denoted as: NaAlg); Urea-formaldehyde resin (denoted as: UF); Citric acid (denoted as: CA); The amount of CMC accounts for 2-7.5wt.% of the mass of the aqueous solution, the amount of NaAlg accounts for 0.5-7.5wt.% of the mass of the aqueous solution, the amount of UF accounts for 0.5-4wt.% of the mass of the aqueous solution, and the amount of CA accounts for 0.2-2.5wt.% of the total mass of CMC, NaAlg and UF.
2. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 1, characterized in that: The following steps are involved: S1, preparing urea-formaldehyde resin (UF); S2, preparing CMC, NaAlg, UF and sodium dodecyl sulfate (SDS) into an aqueous solution and performing a gelatinization reaction; S3, adding citric acid (CA) to carry out polycondensation cross-linking reaction; S4, pouring the solution into a mold, letting it stand and washing it, and finally freeze-drying it to obtain water-retaining slow-release fertilizer granules.
3. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 2, characterized in that: The S1 comprises the following steps: S1.1: preparing an aqueous solution of urea and formaldehyde (FA), adding sodium hydroxide to adjust the pH value, and performing an addition reaction to generate hydroxymethyl urea; S1.2: adding phosphoric acid to adjust the pH value and performing polycondensation reaction to generate UF resin; S1.3: Wash the UF resin with anhydrous ethanol and freeze-dry it.
4. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 3, characterized in that: The step S1.1 comprises: preparing urea and FA into an aqueous solution of 18-20 wt.% (the molar ratio of urea to formaldehyde is U:F=1:2); Among them, urea accounts for 8-10wt.% of the aqueous solution, FA accounts for 8-10wt.% of the aqueous solution, NaOH (0.001mol / L) is added dropwise to adjust the pH of the reaction system to 8-10, and the addition reaction is carried out at a temperature of 50°C for 2h to generate hydroxymethyl urea.
5. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 4, characterized in that: The concentrations of the urea and formaldehyde aqueous solution (FA) are both 9-9.5 wt.%.
6. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 4, characterized in that: S1.2 comprises: adding phosphoric acid (0.001 mol / L) dropwise to adjust the pH of the reaction system to 4-6, and performing polycondensation reaction at 90°C for 2h; During the polycondensation reaction, a white granular precipitate is generated.
7. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 6, characterized in that: The S2 includes: S2.1: CMC, NaAlg and UF are prepared into a 3.5-25wt.% aqueous solution, wherein CMC accounts for 2-7.5wt.% of the mass of the aqueous solution, NaAlg accounts for 0.5-7.5wt.% of the mass of the aqueous solution, and UF accounts for 0.5-2.5wt.% of the mass of the aqueous solution; S2.2: Add 0.5-1.5wt.% of SDS to the aqueous solution and gelatinize in a 60℃ water bath for 3h.
8. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 7, characterized in that: The concentration of the CMC aqueous solution is 5-7.5wt.%, the concentration of the NaAlg aqueous solution is 0.5-1.5wt.%, the concentration of the UF aqueous solution is 0.5-1.5wt.%, and the concentration of the SDS aqueous solution is 1-1.5wt.%; During the reaction, fine white foam appeared in the system.
9. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 6, characterized in that: The S3 includes: S3.1: Take CA and put it into a beaker and add 10 ml of distilled water to dissolve it and add it into the system; wherein the amount of CA is 0.2-2.5wt.% of the total mass of CMC, NaAlg and UF; S3.2: After heating to 80°C, polycondensation and crosslinking reaction were carried out for 3 hours; during the reaction, the white foam in the system decreased.
10. The method for preparing the water-retaining slow-release fertilizer granules for promoting plant growth according to claim 9, characterized in that: The S4 includes: S4.
1. After the reaction is completed, pour the solution into a mold and let it stand at room temperature for 1 hour; S4.2, washing and separation with excess anhydrous ethanol; S4.
3. Place in freeze dryer and dry for 48 hours. The obtained product material is named CMC-NaAlg / UF.